2013
DOI: 10.1159/000346403
|View full text |Cite
|
Sign up to set email alerts
|

Active Eosinophilic Esophagitis Is Associated with Impaired Elimination of Budesonide by Cytochrome P450 3A Enzymes

Abstract: Background/Aims: Topically administered glucocorticoids such as budesonide have the potential of being established as first-line medical treatment of eosinophilic esophagitis (EoE). Safety of budesonide is based on high elimination by cytochrome P450 3A (CYP3A) enzymes. We aimed to investigate systemic absorption and elimination of a new budesonide formulation in patients with active EoE in comparison with healthy controls. Methods: After single and multiple doses of orodispersible budesonide (4 mg/day) the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
(20 reference statements)
0
12
1
Order By: Relevance
“…Previously, it has been shown that only about 9% of budesonide from the effervescent tablet reaches the systemic circulation in patients with active EoE. 20 In contrast, oesophageal fungal infection (hyphae) occurred in some patients receiving budesonide. It is noteworthy that not all macroscopically suspected fungal infections were confirmed by the Grocott staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been shown that only about 9% of budesonide from the effervescent tablet reaches the systemic circulation in patients with active EoE. 20 In contrast, oesophageal fungal infection (hyphae) occurred in some patients receiving budesonide. It is noteworthy that not all macroscopically suspected fungal infections were confirmed by the Grocott staining.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of budesonide effervescent tablets used as mouthwash in patients with oral chronic graft versus host disease or as effervescent tablet for orodispersible use (BET) in patients with active EoE demonstrated a very low systemic bioavailability of budesonide. 19 20 …”
Section: Introductionmentioning
confidence: 99%
“…Budesonide might have increased absorption from the gastrointestinal tract in patients with active inflammation, such as those with EoE. 136 Additionally, because grapefruit inhibits the CYP3A enzyme pathway responsible for the high first-pass effect of budesonide, patients taking this drug should not ingest grapefruit or its juice. 137 Oral candidiasis is uncommon, but esophageal candidiasis was identified in follow-up endoscopies of 15%-20% of patients treated with topical steroids.…”
Section: Treatmentmentioning
confidence: 99%
“…113,114 It is reasonable to consider assessing the effects of both esophageal TCS and PPI on bone mineralization using bone density studies and to assess the absorption of esophageal TCS by checking cortisol levels. [115][116][117] With regard to elimination diets, nutritional guidance should be instituted to gauge whether there is adequate caloric intake and proper vitamin and mineral consumption. Because foods are being eliminated in a population that is allergic and has increased rates of anaphylaxis and food sensitization, the treating clinician should consider the possibility of loss of tolerance to food to which a subject is sensitized.…”
Section: Maintenance Therapymentioning
confidence: 99%